The impact of quantitative platform on candidacy for bronchoscopic lung volume reduction: a multi-center retrospective cohort study - Max Wayne; Suchitra Pilli; Hee Jae Choi; Nathaniel Moulton; Praveen Chenna; Allen Cole Burks; Alexander Chen (Therapeutic Advances in Respiratory Disease)
Background: Bronchoscopic lung volume reduction (BLVR) can be an effective treatment for highly selected patients with severe emphysema but only half of carefully selected patients derive clinical benefit. Two commercially available platforms exist to help determine candidacy for BLVR via quantitative analysis of computed tomography (CT) scans. Objectives: To determine if the two commercially available quantitative platforms identified the same patient population that may benefit from BLVR. Design: A multicenter, retrospective cohort study. Methods: Consecutive patients referred for BLVR between January 1, 2022 and March 31, 2023 at three medical centers in the United States with the same CT scan submitted for quantitative analysis to two commercially available platforms to determine BLVR candidacy were analyzed. The primary outcome of interest was whether quantitative analysis provided different recommendations for individual patients. The recommendation to proceed with BLVR was based on a prespecified algorithm using criteria established in clinical trials for each quantitative platform, respectively. Results: A total of 83 patients referred for BLVR across three centers were included; patients were a median 67 years old, had a median post bronchodilator FEV1 of 30% predicted (IQR: 25, 38), a median residual volume of 220% predicted (IQR: 185, 268), and 29 (34.9%) received endobronchial valves. A total of 26 patients (31.3%) received different recommendations from the two quantitative platforms. Conclusion: In this cohort of patients evaluated for BLVR across multiple medical centers, nearly a third of patients received different recommendations based on the platform utilized for valve assessment. This suggests that the selection process for BLVR may warrant refinement.